Forensic discrimination of black permanent marker pen inks using attenuated total reflection – fourier transform infrared spectroscopy (atr-ftir) with chemometrics procedure - Joseph, Leviana Ferah (2020)
Ink analysis is one of the most important area in forensic document examinations. It involves the analysis of ink of a writing instrument or printer machine. The main purpose of ink analysis is to identify the origin or source of the ink deposited on a substrate such as a paper. Regarding on the ink analysis of pens, study onto marker pen have been received less attention by researchers compared to ink analysis of ballpoint pens and gel pens. Inks analysis involving two types of techniques namely destructive and non-destructive technique. The aim of the present work is to discriminate black permanent marker pen inks of different brands using non-destructive Attenuated total reflectance (ATR) – Fourier transform infrared (FTIR) spectroscopy coupled with Principal Component analysis (PCA) and Linear discriminant analysis (LDA). The discrimination power for visual examinations provides only 47.62% and 28.57%, for direct visual examination and visual examination of IR spectra, respectively. Whereas for PCA and LDA the discrimination power is much higher. PCA provides 81.14% for both raw and standardised dataset and 95.2% for derivatised dataset of discrimination power. LDA provides 95.2%, 76.4% and 100% of correct classification of black marker ink samples for raw, standardised and derivatised dataset, respectively. It can be concluded that the chemometrics procedures, which are, principal component analysis and linear discriminant analysis provide better discrimination of permanent black marker pen inks as compared to visual examinations.